Video Processing Device for Automated Tracking of the Object Identified in Image by the Operator - Boyun, V.P.; Sabelnikov, P.Yu.; Sabelnikov, Yu.A. (Science and Innovation, 2024)
Results of Developing a Video Processing Device for Automated Tracking of the Object Identified in Image by the Operator research project (code VC 200.18.14) have been presented. The required functions of the device have been analyzed. Algorithms, software and hardware for automated tracking of the object identified in image by the operator have been designed.